Regulators and effectors of small GTPases : Rho family - Balch, William Edward, 1949-; Der, Channing J.; Hall, A. (Alan) (Methods in enzymology, 2006)
The Ras superfamily (>150 human members) encompasses Ras GTPases involved in cell proliferation, Rho GTPases involved in regulating the cytoskeleton, Rab GTPases involved in membrane targeting/fusion and a group of GTPases including Sar1, Arf, Arl and dynamin involved in vesicle budding/fission. These GTPases act as molecular switches and their activities are controlled by a large number of regulatory molecules that affect either GTP loading (guanine nucleotide exchange factors or GEFs) or GTP hydrolysis (GTPase activating proteins or GAPs).